EKONOMI KREATIF DALAM PENGELOLAAN SAMPAH DI LINGKUNGAN KAMPUS UNIVERSITAS MUHAMMADIYAH MATARAM - Nur Fitri Hidayanti; Aqodiah Aqodiah; Baiq Ida Astini; Ahmad Hulaimi (El-Khidmat, 2024)
Mataram Muhammadiyah University campus, located at Jalan K.H.Ahmad Dahlan, No. 1, Pagesangan City of Mataram, West Nusa Tenggara. Garbage is a very serious and difficult problem to avoid, the waste generated on the Mataram Muhammadiyah University campus is increasing every year, balanced by the increasing number of students and academics. Mataram Muhammadiyah University itself has difficulty dealing with the waste problem. There are still many members of the UMMAT academic community whose awareness and concern for dealing with waste problems is still lacking. The habit of burning garbage is still ingrained in cleaning workers in dealing with waste problems. The result achieved from this activity is the awareness of the cleaners starting to understand the importance of managing waste. Because not only will it help preserve the environment but it can also help the people's economy with training on creations that can be made from waste and have a sale value. Also with the procurement of trash cans on the Mataram Muhammadiyah University Campus, students and cleaners can carry out real activities in waste management by sorting waste, both organic and non-organic.